2000
DOI: 10.1080/02656730050074096
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and analysis of thermal parameters for the whole-bodyhyperthermia system IRATHERM-2000

Abstract: The infrared system IRATHERM-2000, with water-filtered infrared A wavelength underwent 20 treatments of whole body hyperthermia in conjunction with chemotherapy. In all the sessions, the aimed systemic temperature (41.8 degrees C, maximum 42.0 degrees C) could be achieved and maintained for 60 min. Due to increasing clinical experience, the unnegligible local toxicity, exhibited as heat-induced superficial lesions, and neurotoxicity, could be reduced during the course of the study. Data from three other series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 3 publications
1
42
0
3
Order By: Relevance
“…sCMT was performed under general anaesthesia and was combined with chemotherapy that included the application of folinic acid/5-fluorouracil plus mitomycin (colorectal cancer), ifosfamide (IFO) plus carboplatin (CBCDA) (ovarian cancer) or IFO plus CBCDA plus etoposide (others). For further details on the treatment procedure see Kerner et al (2003), Wust et al (2000) and Hildebrandt et al (2004).…”
Section: Wbh Treatment/chemotherapymentioning
confidence: 99%
“…sCMT was performed under general anaesthesia and was combined with chemotherapy that included the application of folinic acid/5-fluorouracil plus mitomycin (colorectal cancer), ifosfamide (IFO) plus carboplatin (CBCDA) (ovarian cancer) or IFO plus CBCDA plus etoposide (others). For further details on the treatment procedure see Kerner et al (2003), Wust et al (2000) and Hildebrandt et al (2004).…”
Section: Wbh Treatment/chemotherapymentioning
confidence: 99%
“…The disappointing results for WBH may be attributed, in large part, to the inability of current modalities to heat rapidly the body (known to have a protective effect, e.g. Wust et al 11 ), and the complexity of maintaining thermal control of the treatment.…”
Section: Challenge Of Lung Hyperthermiamentioning
confidence: 98%
“…It is suggested that in RWBH [29] 1 h, 85 W power will induce an overall temperature increase of 1 C for a patient weighting 70 kg. The similar observation in Fig.…”
Section: Simultaneous Heating In Selected Vessel Rich Regionsmentioning
confidence: 99%
“…More powerful systems such as long wave infrared hyperthermia can also heat up the patient at a rapid speed, whose standard heating time is about 100e150 min [29]. In this modality, for reduction of heat loss by reactive evaporation, the patient is sealed in the heating chamber where environmental humidity is increased by a nebulizer.…”
Section: Simultaneous Heating In Selected Vessel Rich Regionsmentioning
confidence: 99%